A Multilingual, Multicultural and Multidisciplinary Approach to MTBMLE: A Model for Northern Philippines (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Most Filipinos are multilingual. They can communicate in three or more languages, namely their mother tongue or the vernacular, Filipino, and English, the last two being formally acquired in schools because of the Bilingual Education Policy in the 80s. In the case of Northern Luzon, aside from the three languages, namely, Filipino, the national language, Ilokano, which is the lingua franca of the region, and English, which is the medium of instruction in almost all of the educational institutions, most of the people have other indigenous languages, which also identifies them with their ethnolinguistic groups such as Ibaloy, Kankanay, Isnag, Bontok, Ifugao, Kalinga, Ibanag, Isinay and many more. There are more than fifty languages in North Luzon alone. With this linguistic phenomenon, it is natural to have a classroom with pupils of diverse linguistic backgrounds. This is a reality that teachers in the primary grades face today after implementing the Mother Tongue-Based Multilingual Education (MTB-MLE) in 2012 by RA 10533 in the Philippines. Cognizant of this problem, this paper attempted to present a pedagogical strategy that may be used in such a multilingual setting. This strategy used a text that will have translations in pupils' identified mother tongues. Guided by functional grammar (Halliday 2004, Thompson 2004), the text may be used as a springboard for language analysis-its structure (morphosyntax) and its metafunctions (experiential, interpersonal, and textual)with an intercultural comparison of features found in the text because some lexicons and idioms are exclusive to a particular language and its culture (Sapir, 1949). The text also includes thematic lessons from other disciplines like philosophy, sociology, anthropology in the social sciences and biology, physics, or math in the natural sciences, hence multilingual, multicultural, and multidisciplinary. The proposal is to discuss most of the concepts in a single classroom in two or more sessions a week using the same text; however, the choice of complexity level in terms of structure and content of the instructional material will depend on the teacher who can best assess the cognitive skills of the pupils. This study also discussed the importance and benefits of multilingualism to individuals and communities, and institutions and why it must be introduced as early as possible. It must be sustained in the educational system with the active involvement and participation of other institutions.
Keywords: MTBMLE model, Northern Luzon, pedagogical approach